Answer:
Hence a = 3.66 and -3.628
b = 0.834 and -2.634
Explanation:
Given the equations
a-2b =2 -------- (1)
a²+b²+2a -3b =19 --------(2).
From 1;
a = 2 + 2b
Substitute into 2
(2+2b)²+b²+2a -3b =19
Expand
4 + 8b + 4b²+b²+2(2+2b)-3b = 19
4b²+b²+8b+4b+4+4-3b = 19
5b²+9b+8 = 19
5b²+9b-11 = 0
b = -9±√81+4(55)/2(5)
b= -9±√301/10
b = -9+17.34/10 and -9-17.34/10
b = 8.34/10 and -26.34/10
b = 0.834 and -2.634
Since a = 2+2b
a = 2+2(0.834)
a= 2 +1.668
a = 3.668
Also
a = 2+2(-2.634)
a = 2 - 5.628
a = -3.628
Hence a = 3.66 and -3.628
b = 0.834 and -2.634